Cartografía de lo sagrado. Una exploración en la espiritualidad malécu - Madrigal, Víctor (2019)
The spirituality of the Malécu people shapes a particular vision of the world, in which their deities, Tócu maráma, dwell in the rivers of the ancestral territory; to the physical conformation of the territory lies a sacred cartography with deep symbolic imbrications in the way of understanding themselves and how they base the dynamism of social relations, and, ultimately, how they are bounded to nature and in a particular way to the earth, a returning point when dying. The underground is a meeting space with relatives and with all people who during their lifetime followed the divine rules. Keywords: The sacred, spirituality, indigenous people, territory